The effectiveness between biological and chemical method in controlling rats population in oil palm plantation at Mados’s Lenggor, Kahang, Johor / Muhammad Safbihin Safbani - Safbani, Muhammad Safbihin (Faculty of Plantation and Agrotechnology, 2017)
Oil palm is one of major crop as this crop could generate high income and profit and also encourage the development of economy in Malaysia. However there are various obstacles like pest and disease that limits the production of oil palm and its sustainability. The rat species is mostly the dominant pest in Malaysia Oil Palm Plantation. There are three species of rats which are Rattus tiomanicus, Rattus argentiventer, and Rattus rattus diardii. They tend to attack the oil palm tree mostly at the bunches part and gives a serious damage to the Oil Palm trees which eventually reduce the rate of oil palm yield production. Based on individual species, R. tiomanicus was reported in 68% of the estates, followed by R. argentiventer 46% and R. rattus diardii 28%. Most of the oil palm plantation have two methods that are commonly been used in controlling rat population which are biological control and chemical control. The using of rodenticide as a chemical control while Tyto alba ( Barn Owl) represented the biological control mostly are used as major control method in order to eradicate the rats population in Oil Palm Plantation.